Strategies for Developing CRISPR‐Based Gene Editing Methods in Bacteria. Issue 2 (19th November 2019) - Wu, Zhaowei; Wang, Yujue; Zhang, Yifei; Chen, Weizhong; Wang, Yu; Ji, Quanjiang
Abstract: Gene editing is a fundamental technique for the identification of the linkages from genetic determinants to significant biological phenotypes, and the engineering of industrial strains to produce fine chemicals. Recently, the primitive bacterial immunity systems, clustered regularly interspaced short palindromic repeat (CRISPR)‐Cas systems, have been engineered as programmable nucleases to deliver double‐strand breaks (DSBs) at user‐defined loci. The DSB is repaired via either homology‐direct repair or the non‐homologous end joining pathway, generating a mutant in various organisms, and leading a revolution in the field of gene editing. This paper reviews the structural and molecular details of CRISPR‐Cas systems, describing their applications and challenges of genome targeting in bacterial cells. Moreover, the DSB repair pathways in bacteria are summarized and a guideline for selecting repair machines and maximizing the recombination efficiency is presented. In addition, the plasmid curing approaches in bacteria are outlined for iterative gene editing or downstream biological applications. Furthermore, CRISPR‐based transcriptional regulation, base editing, and transposition are also introduced. Finally, this paper prospects the future directions for improving CRISPR‐based gene editing methods in bacteria. Abstract : Recent progress and molecular details on clustered regularly interspaced short palindromic repeat (CRISPR)‐based gene editing in bacterial species are summarized. CRISPR/Cas systems are exploited to introduce DNA breaks on desired loci. By using a set of repair machines, various mutations (deletions, insertions, or substitutions) are generated. Their applications facilitate the studies in bacterial genetics and boost the metabolic engineering for industrial purposes.